The Value, Purpose and Pilot Project of University Smart Sports Service System - YU SUN; OOI BOON KEAT (International Journal of Multidisciplinary Research and Studies, 2024)
To explore the value and purpose of the construction of the smart sports service system in universities, to analyze the detailed rules of the system construction through the pilot research, and to put forward the suggestions and prospects. Research results: Value mainly refers to the construction of a higher level of national fitness public service system, driving the integration and transformation of university sports service, and improving the participation of teachers and students through efficient supply. The basic purpose include local conditions, people-oriented, on-demand configuration and green innovation; The system construction is mainly reflected in the comprehensive construction of smart stadiums, ecological layout, platform service and background management. In view of the development of smart sports into university sports service and combined with the development status of smart sports industry, this paper puts forward some feasible suggestions. Looking into the future, science and technology will enable universities to build a smart sports service system with a higher level, wider dimension and deeper integration.